Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve this problem step-by-step, we need to analyze and compare the two given equations: [tex]\(2x = 0\)[/tex] and [tex]\(ax + by + c = 0\)[/tex].
1. Understanding the first equation:
[tex]\[ 2x = 0 \][/tex]
When we solve for [tex]\(x\)[/tex], we get:
[tex]\[ x = 0 \][/tex]
2. Substitute [tex]\(x = 0\)[/tex] into the second equation:
[tex]\[ ax + by + c = 0 \][/tex]
Substituting [tex]\(x = 0\)[/tex] into the equation, we get:
[tex]\[ a(0) + by + c = 0 \implies by + c = 0 \][/tex]
3. Interpreting this equation:
Since [tex]\(by + c = 0\)[/tex] must hold for all values of [tex]\(y\)[/tex], the simplest way to satisfy this equation is if [tex]\(b\)[/tex] and [tex]\(c\)[/tex] are such that their combination renders the equation true regardless of [tex]\(y\)[/tex].
By comparison and assuming the typical coefficient values, we find:
[tex]\[ a = 2, \quad b = 1, \quad c = 0 \][/tex]
4. Sum of the coefficients:
Now, compute [tex]\(a + b + c\)[/tex]:
[tex]\[ a + b + c = 2 + 1 + 0 = 3 \][/tex]
Thus, the value of [tex]\((a + b + c)\)[/tex] is:
[tex]\[ 3 \][/tex]
1. Understanding the first equation:
[tex]\[ 2x = 0 \][/tex]
When we solve for [tex]\(x\)[/tex], we get:
[tex]\[ x = 0 \][/tex]
2. Substitute [tex]\(x = 0\)[/tex] into the second equation:
[tex]\[ ax + by + c = 0 \][/tex]
Substituting [tex]\(x = 0\)[/tex] into the equation, we get:
[tex]\[ a(0) + by + c = 0 \implies by + c = 0 \][/tex]
3. Interpreting this equation:
Since [tex]\(by + c = 0\)[/tex] must hold for all values of [tex]\(y\)[/tex], the simplest way to satisfy this equation is if [tex]\(b\)[/tex] and [tex]\(c\)[/tex] are such that their combination renders the equation true regardless of [tex]\(y\)[/tex].
By comparison and assuming the typical coefficient values, we find:
[tex]\[ a = 2, \quad b = 1, \quad c = 0 \][/tex]
4. Sum of the coefficients:
Now, compute [tex]\(a + b + c\)[/tex]:
[tex]\[ a + b + c = 2 + 1 + 0 = 3 \][/tex]
Thus, the value of [tex]\((a + b + c)\)[/tex] is:
[tex]\[ 3 \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.